Reduced cytomegalovirus reactivation and viremia without increasing GVHD after URD-PBSCT: A prospective study using targeted ATG dosing strategy - Chen, Sheng; Wang, Lu; Luan, Songhua; Wang, Haitao; Du, Jishan; Ge, Dongxue; Li, Fei; Wu, Yongli; Gu, Zhenyang; Dou, Liping; Liu, Daihong (Cancer pathogenesis and therapy, 2025)
Anti-thymocyte globulin (ATG) is widely used in allogeneic hematopoietic stem cell transplantation (allo-HCT) to prevent severe graft-versus-host disease (GVHD) and graft failure. Insufficient ATG exposure may reduce its effectiveness in GVHD prophylaxis, while excessive exposure can elevate the risk of viral reactivation, non-relapse mortality (NRM), and disease relapse. Based on monitoring ATG (Thymoglobulin, Sanofi, Lyon, France) concentrations, we developed an ATG-targeted dosing strategy and conducted a prospective, single-arm study on patients undergoing unrelated donor peripheral blood stem cell transplantation (URD-PBSCT) to evaluate its efficacy and safety. We enrolled 30 patients with malignant hematological diseases who underwent URD-PBSCT between January 2020 and June 2023. All patients received an ATG-targeted dosing strategy, involving a 4-day administration of ATG: 1.5 mg/kg on day −5, 2.5 mg/kg on day −4, with dose adjustments on day −3 and day −2 to achieve an optimal area under the concentration–time curve (AUC) for active ATG. Engraftment, viral infections, acute and chronic GVHD, relapse, and survival outcomes were statistically analyzed. A historical cohort of 38 patients who underwent URD-PBSCT between December 2014 and December 2020 was used for comparison. Patients in the historical cohort received a fixed total dose of 10 mg/kg ATG from day −5 to day −2. All patients in the targeted dosing cohort achieved successful neutrophil and platelet engraftment with 100% donor chimerism. The cumulative incidence of cytomegalovirus (CMV) reactivation and persistent CMV viremia at 180 days post-transplantation was 30.0% and 16.7%, respectively. The cumulative incidences of Epstein–Barr virus (EBV) reactivation and persistent EBV viremia at 180 days were 46.7% and 23.3%, respectively. The cumulative incidences of grades II–IV and III–IV acute GVHD at 100 days were 49.4% and 9.3%, respectively. The 1-year cumulative incidence of relapse (CIR) was 10.0%, the 1-year NRM was 10.0%, the 1-year disease-free survival (DFS) was 80.0%, and the 1-year overall survival (OS) was 86.7%. Compared with the historical cohort, the targeted dosing cohort showed significantly lower the cumulative incidences of CMV reactivation (30.0% vs. 78.9%, P < 0.001) and persistent CMV viremia (16.7% vs. 42.1%, P = 0.026) on day 180. However, no significant differences were observed in EBV reactivation (46.7% vs. 68.4%, P = 0.170) or persistent EBV viremia (23.3% vs. 44.7%, P = 0.075) on day 180. Similarly, there were no statistically significant differences in the cumulative incidences of grade II–IV (49.4% vs. 50.3%, P = 0.700) or grade III–IV (9.3% vs. 18.8%, P = 0.390) acute GVHD on day 100, or 1-year chronic GVHD (10.0% vs. 13.2%, P = 0.680). Utilizing a targeted ATG dosing strategy in URD-PBSCT resulted in a lower incidence of CMV reactivation and viremia without increasing the risk of acute or chronic GVHD. www.clinicaltrials.gov, NCT06572462. [Display omitted] •This prospective, single-arm study explored the optimal dosing regimen of anti-thymocyte globulin (ATG) in unrelated donor peripheral blood stem cell transplantation (URD-PBSCT) under myeloablative conditioning.•Adjusted ATG on days −3 and −2 reduced cytomegalovirus (CMV) reactivation and viremia at +180 days, prevented graft-versus-host disease (GVHD), and promoted engraftment.•ATG-targeted dosing from haplo-PBSCT demonstrated good safety and efficacy in URD-PBSCT, guiding future ATG dosing studies.